Time-Temperature Superposition to Determine the Stress-Rupture of Aramid Fibres - Alwis, K. G. N. C.; Burgoyne, C. J. (Applied composite materials, 2006)
Conventional creep testing takes a long time to obtain stress-rupture data for aramid fibres at the low stress levels likely to be used in practical applications. However, the rate of creep of aramid can be accelerated by a thermally activated process to obtain the failure of fibres within a few hours. It is possible to obtain creep curves at different temperature levels which can be shifted along the time axis to generate a single curve know as a master curve, from which stress-rupture data can be obtained. This technique is known as the time-temperature superposition principle and will be applied to Kevlar 49 yarns. Important questions relating to the techniques needed to obtain smooth master curves will be discussed, as will the validity the resulting curves and the corresponding stress-rupture lifetime.[PUBLICATION ABSTRACT]